Directing 'The Absolute' : towards destabilising the victim/perpetrator binary in Sam Shepard's A lie of the mind (1985) - Coetzee, Marie-Heleen (University of Pretoria, 2017)
Dissertation (MA)--University of Pretoria, 2016.